Transmissions and transformations : learning through the arts in Asia - Vatsyayan, Kapila; Vatsyayan, Kapila; India International Centre (Delhi : Primus Books, 2011)
Contributed articles presented at an international symposium, organized in collaboration with UNESCO Regional Office, Bangkok and the Center of International Arts Education, New York, held at New Delhi in 2005.
"India International Centre."
Includes bibliographical references and index.
Keywords: Culture -- Study and teaching -- Asia -- Congresses